Low Concentrations of Recombinant Factor VIIa May Improve the Impaired Thrombin Generation of Glanzmann Thrombasthenia Patients - Levy-Mendelovich, Sarina; Levy, Tamara; Budnik, Ivan; Barg, Assaf Arie; Rosenberg, Nurit; Seligsohn, Uri; Kenet, Gili; Livnat, Tami (Thrombosis and Haemostasis, 2019)
Introduction Glanzmann thrombasthenia (GT) is a rare bleeding disorder. The disease is caused by the lack or dysfunction of platelet membrane glycoprotein IIb/IIIa (integrin αIIbβ3) which is essential for platelet aggregation. Bleeding episodes are usually managed by platelet transfusions. Recombinant activated factor VII (rFVIIa) is a common adjunct or alternative treatment option.Objective This article evaluates GT patients' response to increasing concentrations of rFVIIa using an ex vivo thrombin generation assay to elaborate the knowledge in which rFVIIa treats a platelet dysfunction for bleeding episodes and preoperative management.Materials and Methods Twenty-four GT patients in a non-bleeding state were enrolled into the study. Thrombin generation was measured in platelet-rich plasma (PRP) in the presence of 0.7 to 7.0 µg/mL rFVIIa. Clinical data of rFVIIa used to treat GT patients' bleeding episodes was collected, and patients' follow-up course was documented.Results Thrombin generation was significantly decreased in GT patients compared with controls. An individual response to rFVIIa spiking was noted in GT patients' PRP. In the majority of patients, a significant improvement in thrombin generation was already demonstrated with low concentrations (0.7 µg/mL) of rFVIIa.Conclusion Thrombin generation is improved in the majority of GT patients following ex vivo spiking with rFVIIa. The magnitude of this improvement is individual and was noted at low concentrations of rFVIIa. There is a need for a prospective clinical trial to find the optimal doses or rFVIIa for treatment of GT patients.
Keywords: Glanzmann thrombasthenia; thrombin generation; rFVIIa